Baby steps millionaires : how ordinary people built extraordinary wealth-and how you can too - Ramsey, Dave (Ramsey Press, The Lampo Group, LLC, 2021)
"You can baby step your way to becoming a millionaire. Most people know Dave Ramsey as the guy who did stupid with a lot of zeros on the end. He made his first million in his twenties--the wrong way--and then went bankrupt. That's when he set out to learn God's ways of managing money and developed the Ramsey Baby Steps. Following these steps, Dave became a millionaire again-this time the right way. After thirty years and millions of lives changed, the evidence is undeniable: if you follow the Baby Steps, you will become a millionaire."--Publisher.